The dative in Croatian as a dominion phenomenon - Stanojević, Mateusz-Milan (Array, 2008)
The aim of the paper is to outline a semantically coherent view of the dative case in Croatian. More specifically, our claim is that the semantic coherence of the Croatian dative hinges on the notion of the speaker's dominion. Speaker's dominion signals the availability of a particular element for interaction to a participant, the possibility of its influence on the participant, the location of the element with regard to a familiar participant, and requires the participant to be conscious or some other type of prominent entity. In order to check whether the Croatian dative is a dominion phenomenon, we performed two corpus studies of the Croatian National Corpus to find nouns and pronouns in the dative case, and performed a semantic analysis. The results have shown that the Croatian dative case exhibits all of the semantic characteristics of a dominion phenomenon. Future research should focus on establishing the dative schema in Croatian and on additional issues (such as the dative's affinity to the middle voice). This may lead to some general limiting factors in the notion of mental access.